2022
DOI: 10.1002/anie.202216838
|View full text |Cite
|
Sign up to set email alerts
|

Crystalline Unipolymer Monolayer with High Modulus and Conductivity

Abstract: The synthesis of crystalline polymer with a well-defined orientated state and a two-dimensional crystalline size beyond a micrometer will be essential to achieve the highest physical feature of polymer material but remain challenging. Herein, we show the synthesis of the crystalline unipolymer monolayer with an unusual ultrahigh modulus that is higher than the ITO substrate and high conductance by simultaneous electrosynthesis and manipulation. We find that the polymer monolayer has fully extended in the verti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 56 publications
1
31
1
Order By: Relevance
“…S61). These modular values are almost the highest among all organic materials ( 29 ). The highly uniform and modular monolayers with similar values in thicknesses (21 to 23 nm) and theoretical molecular lengths (22 to 23 nm) (figs.…”
Section: Resultsmentioning
confidence: 93%
“…S61). These modular values are almost the highest among all organic materials ( 29 ). The highly uniform and modular monolayers with similar values in thicknesses (21 to 23 nm) and theoretical molecular lengths (22 to 23 nm) (figs.…”
Section: Resultsmentioning
confidence: 93%
“…20 Another successful strategy has been developed to fabricate two-dimensional (2D) hybrid sp/sp 2 graphdiyne or related carbon rich systems with a 2D structure. [20][21][22][23][24][25][26][27][28] All the above studies have experimentally confirmed the importance of novel carbon allotropes comprising a quantitative content of sp-hybridized carbon and their unusual properties. Compared to sp 2 and sp 3 hybridized carbon, sp carbon shows affinity to certain metal atoms or organic molecules with particular functional groups, which makes carbon material containing sp carbon exhibit broad development space in the fields of selected adsorption, deposition and separation.…”
mentioning
confidence: 89%
“…15d). 175 The strong interaction between metal ions and the alkyne bond makes the growth of GDY present a state of eneyne complex in the inner layer and gradient GDY bond in the outer layer. The Cu and O vacancies enhance the ion transport kinetics of the Cu 0.95 V 2 O 5 @GDY phase and increase the lithium storage sites.…”
Section: Electrical and Electrochemical Propertiesmentioning
confidence: 99%